Targeting Niche Tourism Using Niche Media: Expanding the Media in a Digital Era towards the Hashtag Generation - Febrian Febrian (Proceedings, 2022)
Niche tourism is an umbrella term to show that certain activities serve a specialized segment of the tourism industry for their tourists. Facing new direction in tourism, a niche market also needs a niche marketing medium. This paper shows how certain media used to gather information for destination selection process can effectively create a better perceived image than other media. The data for this paper were collected using questionnaires aiming at the hashtag generation age groups. These age groups will be the potential marketing targets in near future. Approximately 250 questionnaires were collected with responses on where they obtained information about their dream destination and what reasons caused the medium they used to be the best source of information. In this modern era, where information moves fast and can be obtained via various media, different media can create different perceived images of tourist destinations. This paper is intended to show the opportunity for expanding the availability of segmentation that has potentials for niche marketing and for creating a new niche segmentation in the future, either though the medium used to promote the destination or expanding the destination itself.